Ionization and electron capture in 240 keV Kr8+ collisions with CO2. (July 2015) - Bhatt, Pragya; Sairam, T; Kumar, A; Kumar, H; Safvan, C P
Synopsis: The dissociation of CO2 q+ ions is studied in slow Kr 8+ ion collisions with a CO2 molecule using the technique of recoil ion momentum spectroscopy and multiple ion coincidence.